SCREENING INVESTIGATION OF SOME NUMERICAL ABERRATIONS AT PATIENTS WITH ACUTE MYELOID LEUKEMIA BY FISH METHOD IN INTERPHASE CELLS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Numerical aberrations of 19 patients with acute myeloid leukemia have been studied by the technique of Fluorescence in situ hybridization (FISH) in interphase cells. The centromere specific DNA probes for chromosomes 8, 10, 11, 7, X and Y were prepared in the Department of Genetics and Cytology of YSU. We revealed different numerical aberrations of tested chromosomes (not less than 3%) at 10 patients. Near-tetraploidy was found at one of them. FISH method in interphase cells allowed to reveal cytogenetic abnormalities at patients with AML, as the conventional cytogenetic analysis is inaccessible, and screening application is recommended by us.
Keywords: myeloid leukemia; chromosomes 8, 10, 11, 7, X and Y; numerical aberrations; near-tetraploidy